Dari Scrolling ke Shopping: Personalisasi Konten FYP dalam Mendorong Perilaku Belanja Impulsif di TikTok Shop - Satria Veriansyah Wiguna; Muhammad Syihabuddin; Farhan Maulana Athallah; Pradipta Kurniawan Herlambang (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The main focus of this study is to examine how the personalization of For You Page (FYP) content functions as a marketing instrument that stimulates impulsive shopping among TikTok Shop users. Using a descriptive qualitative methodology, this study applies a purposive sampling technique targeting active TikTok users with experience in unplanned transactions. Data was collected through in-depth interviews, observation of promotional content, and documentation, then analyzed through reduction, presentation, and conclusion drawing. The study findings confirm that personal curation through content that becomes FYP as one of the strategies in digital marketing and psychological factors in the form of FOMO are the main triggers for spontaneous shopping. The integration of entertainment content, recommendation systems, and transaction access strengthens the effectiveness of TikTok Shop in the context of social commerce. This proves that personalized recommendation systems do not merely filter content but act as marketing instruments that reconstruct digital consumption patterns and provide insights for developing more adaptive business strategies in the future.